2022
DOI: 10.1002/adts.202100400
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure, Bonding, and Stability of Boron Subphthalocyanine Halides and Pseudohalides

Abstract: Halides and pseudohalides of boron subphthalocyanine (BsubPc) are promising candidates for efficient yet stable organic photovoltaics. Here, the electronic structure of such molecules, obtained using density functional theory, is considered. Based on the calculations, it is found that the tetrameric boron bond is stabilized by an inductive effect at the axial substituent and by conjugative effects across the ring system. It is further found that stability is dictated mostly by the axial moiety, such that Br-Bs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Only axially fluorinated hybrids were cast into thin films since our samples of Cl-F 8 Bsub­(Pc 2 -Nc 1 ) were mixtures containing residual F-F 8 Bsub­(Pc 2 -Nc 1 ) from random axial halide exchange and slight hydrolysis in the form of HO-F 8 Bsub­(Pc 2 -Nc 1 ). Our samples of Cl-F 8 BsubPc had relatively high purity at >99% post sublimation, but this hybrid was not introduced into thin films due to the hydrolytic susceptibility of the B–Cl bond Figure b illustrates the photophysical properties of the axially fluorinated hybrids in solid-state thin films, and these properties are compared to those observed in solution in Table .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only axially fluorinated hybrids were cast into thin films since our samples of Cl-F 8 Bsub­(Pc 2 -Nc 1 ) were mixtures containing residual F-F 8 Bsub­(Pc 2 -Nc 1 ) from random axial halide exchange and slight hydrolysis in the form of HO-F 8 Bsub­(Pc 2 -Nc 1 ). Our samples of Cl-F 8 BsubPc had relatively high purity at >99% post sublimation, but this hybrid was not introduced into thin films due to the hydrolytic susceptibility of the B–Cl bond Figure b illustrates the photophysical properties of the axially fluorinated hybrids in solid-state thin films, and these properties are compared to those observed in solution in Table .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our samples of Cl-F 8 BsubPc had relatively high purity at >99% post sublimation, but this hybrid was not introduced into thin films due to the hydrolytic susceptibility of the B−Cl bond. 76 Figure 6b illustrates the photophysical properties of the axially fluorinated hybrids in solid-state thin films, and these properties are compared to those observed in solution in Table 1. The thin-film data was found to be similar to the data acquired from dilute toluene solutions.…”
Section: Solid-state Uv−vis Absorption and Emissionmentioning
confidence: 99%
“…Very strong electron-withdrawing groups in one region of the molecule can pull electron density away from another region and make is susceptible to reaction. For BsubPcs, the axial boron-halogen bond is vulnerable to be attacked by a water vapor molecule which reacts to create a boron–hydroxy bond that is thermodynamically favorable. , This hydroxy bond formation can occur during synthesis and subsequent purification, yet in the production of the BsubPcs throughout this study, we were able to avoid the hydroxy bond formation. We have in the past checked the hydroxy BsubPc performance within a device and found it has lower conductivity.…”
Section: Discussionmentioning
confidence: 96%
“…We had shown that axial substitution from chlorine to a phenoxy group takes between 2-8 hours, we assumed that 4 hours would be a reasonable amount of time due to the lability of bromines in the axial position. 7 Past work in the lab had also shown with the synthesis of Br-Cl6BsubPc, without any additional catalysts, the synthetic process underwent random axial halide exchange in which the product yielded a Br0.27|Cl0.73-Cl6BsubPc mixture, 4 helping support our theory of running the reaction for 4 hours. However, there were a lack of additional analytics available while developing this synthetic process.…”
Section: Resultsmentioning
confidence: 67%